2020
DOI: 10.35944/jofrp.2020.9.1.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Access to Debt on Lebanese Small and Medium Enterprises Performance

Abstract: Since thirties access to debt has been considered as one of the main challenges facing the growth of Small and medium-sized enterprises (SMEs). Therefore, empirical studies focused on how facilitating access to debt affects SMEs financial performance in developed countries. However, this is not the case in the developing economies countries such as Lebanon due to the lack of financial transparency and poor financial reporting. In addition, very few studies discussed the theoretical pillar behind SMEs financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…(Denervaud, Johnson, & Soumoy, 2009). Lebanese SMEs could implement measures to support the economy and exceptional arrangements for the repayment of their debts to banks (Jadoua & Mostapha, 2020). To address the liquidity challenges faced by local businesses, the Central Bank of Lebanon has proposed a temporary solution through Circular No.…”
Section: Discussionmentioning
confidence: 99%
“…(Denervaud, Johnson, & Soumoy, 2009). Lebanese SMEs could implement measures to support the economy and exceptional arrangements for the repayment of their debts to banks (Jadoua & Mostapha, 2020). To address the liquidity challenges faced by local businesses, the Central Bank of Lebanon has proposed a temporary solution through Circular No.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we contribute to the extant literature in two relevant ways. First, we extend the growing literature that investigates capital structure drivers in MENA regions (Al-Smadi, 2019;Ayed & Zouari, 2014;Gharaibeh & Al-Tahat, 2020;Jadoua & Mostapha, 2020;Soufeljil et al, 2017) which focused on SMEs characteristics. In our study, we examine the impact of some attributes of CEOs (entrepreneur experience, university degree and gender) on financing patterns.…”
mentioning
confidence: 94%
“…Second , tapping into organizational lifecycle (Churchill & Lewis, 1983; Dodge et al, 1994), these effects could be moderated by firm age. Although previous studies have investigated firm age effect on capital structure (Jadoua et & Mostapha, 2020; Mahmud & Akin, 2019; Youssef, 2019), they did not consider the interaction of life cycles with entrepreneurs' attributes. Inclusion of these attributes could explain the mixed findings of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research related to microcredit programs has been conducted, such as research at microfinance institutions in Mongolia, India, and Lebanon, which found that microcredit has a positive impact on business performance in the country, especially from the profits and income of small and medium enterprises (Attanasio, O., et al, 2015;Banerjee, A., et. al., 2015;Jadoua, Z. A., et.…”
Section: Introductionmentioning
confidence: 99%